2023
DOI: 10.1021/acs.chemmater.2c03125
|View full text |Cite
|
Sign up to set email alerts
|

Manipulation of the Structure and Optoelectronic Properties through Bromine Inclusion in a Layered Lead Bromide Perovskite

Abstract: One of the great advantages of organic–inorganic metal halides is that their structures and properties are highly tuneable and this is important when optimizing materials for photovoltaics or other optoelectronic devices. One of the most common and effective ways of tuning the electronic structure is through anion substitution. Here, we report the inclusion of bromine into the layered perovskite [H3N(CH2)6NH3]PbBr4 to form [H3N(CH2)6NH3]PbBr4·Br2, which contains molecular bromine (Br2) intercalated between the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 72 publications
0
2
0
Order By: Relevance
“…Furthermore, 1,4-BDA in these 2D perovskites adopts partial gauche or eclipsed conformation, and we anticipate the butane chain will adopt all-anti conformation (i.e., fully staggered) at higher temperatures, as was observed in our earlier layered double perovskites with this cation, 25 and di-ammonium cations with higher number of carbons. 39 We could see broad peak like features in the DSC curves (Fig. S12 †) on heating which might be due to the expected phase transition induced by such conformational changes in 1,4-BDA.…”
Section: Dalton Transactions Communicationmentioning
confidence: 86%
“…Furthermore, 1,4-BDA in these 2D perovskites adopts partial gauche or eclipsed conformation, and we anticipate the butane chain will adopt all-anti conformation (i.e., fully staggered) at higher temperatures, as was observed in our earlier layered double perovskites with this cation, 25 and di-ammonium cations with higher number of carbons. 39 We could see broad peak like features in the DSC curves (Fig. S12 †) on heating which might be due to the expected phase transition induced by such conformational changes in 1,4-BDA.…”
Section: Dalton Transactions Communicationmentioning
confidence: 86%
“…It was also shown that based on pentaiodobismutate linked by 1,6-diaminohexane bridges, it is possible to create a molecular ferroelectric semiconductor, and it is also possible to create its thin films [47]. Last year, a work was published where layered lead perovskites were studied, in which the layers were formed with protonated 1,6-diaminohexane bridges [48]. 1,6-diaminohexane can be used to obtain self-assembled hybrid layered molybdates [49], photo-electroactive indium and antimony chalcogenides [50], dynamic organic-inorganic hybrid [H 2 dahx]ZnBr 4 crystals with the ability to control phase transitions [51], and hybrid organic-inorganic borate frameworks [52].…”
Section: Introductionmentioning
confidence: 99%